DIGITAL COMMUNICATIONS - A MODERN VECTOR OF MARKETING DEVELOPMENT OF COMPANIES - ANDRUSHKEVYCH, Zinayida; BOIKO, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article highlights the relevance of using digital communications tools as one of the modern directions of a company's marketing development in the context of rapid technological development. The author focuses on digital communication channels used to attract and retain consumers in the online environment. The main tools of digital communications in the marketing policy of companies are considered, in particular, new media, email marketing, contextual and targeted advertising, SMM, Influence Marketing, content marketing, SEO, mobile marketing and others aimed at individualized interaction with the audience through various digital channels and technologies. The author analyzes the importance of digital communication tools for successful interaction with consumers in the modern digital environment.It is noted that for effective interaction with consumers, companies should interact with them through digital communications at all stages of the purchase, from awareness of the need to obtaining a positive consumer experience.The article considers key performance indicators (KPIs) of digital communications, such as website traffic, time spent on the website, conversion, social media engagement, ROI, number of applications and sales, CTR, number of email newsletter subscribers, and others, which help to assess the effectiveness of the company's marketing development activities in the online environment and take measures to improve them in accordance with the company's business goals.The author concludes that digital communications have become an integral factor in the development of marketing for modern companies, as they allow for effective interaction with the audience through interactivity, personalization and omnichannel approach, which helps to improve real-time interaction with customers and achieve optimal business results.Keywords: digital communications, marketing development, digital channels, customer interaction, key performance indicators (KPIs), personalization.
Keywords: digital communications; marketing development; digital channels; customer interaction; key performance indicators (KPIs); personalization